Advancing AI-Driven Geospatial Analysis and Data Generation: Methods, Applications and Future Directions - Hartwig H. Hochmair; Levente Juhász; Hao Li (ISPRS International Journal of Geo-Information)
Recent years have witnessed a revolution of artificial intelligence (AI) technologies, highlighted by the rise of generative AI and geospatial artificial intelligence (GeoAI) [...]